2006
DOI: 10.1158/0008-5472.can-05-2769
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphatidylinositol 3-Kinase Destabilizes Mycn Protein and Blocks Malignant Progression in Neuroblastoma

Abstract: Amplification of MYCN occurs commonly in neuroblastoma. We report that phosphatidylinositol 3-kinase (PI3K) inhibition in murine neuroblastoma (driven by a tyrosine hydroxylase-MYCN transgene) led to decreased tumor mass and decreased levels of Mycn protein without affecting levels of MYCN mRNA. Consistent with these observations, PI3K inhibition in MYCN-amplified human neuroblastoma cell lines resulted in decreased levels of Mycn protein without affecting levels of MYCN mRNA and caused decreased proliferation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(205 citation statements)
references
References 39 publications
(41 reference statements)
11
190
2
Order By: Relevance
“…A recent study indicated that a direct consequence of inhibiting the PI3K/Akt pathway in certain neuroblastoma cell lines is the destabilization of N-myc protein (Chesler et al, 2006). Since we found that ARC inhibits the Akt pathway in neuroblastoma cells, we decided to check if N-myc protein levels are affected.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 99%
“…A recent study indicated that a direct consequence of inhibiting the PI3K/Akt pathway in certain neuroblastoma cell lines is the destabilization of N-myc protein (Chesler et al, 2006). Since we found that ARC inhibits the Akt pathway in neuroblastoma cells, we decided to check if N-myc protein levels are affected.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 99%
“…The F1174L ALK mutation is associated preferentially with MYCN amplification in NB and induces constitutive activation of the PI3K/AKT pathway [9,10]. This constitutive activation leads to oncogenic stabilization of MYCN protein [11]. Poorly differentiated NB with high expression of MYCN and the F1174L ALK mutation define a subset of patients with high-risk NB [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the mouse TH-MYCN neuroblastoma model it has been shown that inhibition of PI3-kinase activity destabilises MYCN protein and blocks malignant progression in neuroblastoma. 22 The regulation of the complex signalling networks involved in MYCN protein degradation is far from clear, but PI3-kinase and its downstream targets appear to have a critical role in the expression and stability of MYCN in neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%